Asylum seekers' and Refugees' Changing Health (ARCH) study protocol: an observational study in Lebanon and Denmark to assess health implications of long-distance migration on communicable and non-communicable diseases and mental health. Issue 5 (26th May 2020) - Eiset, Andreas Halgreen; Aoun, Michaelangelo P; Haddad, Ramzi S; Naja, Wadih J; Fuursted, Kurt; Nielsen, Henrik Vedel; Stensvold, Christen Rune; Nielsen, Monica Stougaard; Gottlieb, Annemarie; Frydenberg, Morten; Wejse, Christian
Abstract : Introduction: By end of 2018, the European Union countries hosted approximately 2.5 million refugees and Lebanon alone hosted more than 1 million. The majority of refugees worldwide came from Syria. The prevailing study design in published studies on asylum seekers' and refugees' health leaves a number of fundamental research questions unanswerable. In the Asylum seekers' and Refugees' Changing Health (ARCH) study, we examine the health of a homogeneous group of refugees and asylum seekers in two very different host countries with very different migration histories. We aim to study the health impact of the migration process, living conditions, access to healthcare, gene–environment interactions and the health transition. Methods and analysis: ARCH is an international multisite study of the health of adult (>18 years old) Syrian refugees and asylum seekers in Lebanon and Denmark. Using a standardised framework, we collect information on mental and physical health using validated scales and biological samples. We aim to include 220 participants in Danish asylum centres and 1100 participants in Lebanese refugee camps and settlements. We will use propensity score weights to control for confounding and multiple imputation to handle missing data. Ethics and dissemination: Ethical approval has been obtained in Lebanon and Denmark. In the short term, we will present the cross-sectional association between long-distance migration and the results of the throat and wound swab, blood and faeces samples and mental health screenings. In the longer term, we are planning to follow the refugees in Denmark with collection of dried blood spots, mental health screenings and semistructured qualitative interviews on the participant's health and access to healthcare in the time lived in Denmark. Here, we present an overview of the background for the ARCH study as well as a thorough description of the methodology.